Associations between pre-employment immunologic and airway mucosal factors and the development of occupational allergy - Krop, Esmeralda J M; Heederik, Dick J J; Lutter, René; de Meer, Gea; Aalberse, Rob C; Jansen, Henk M; van der Zee, Jaring S (Elsevier Inc., 2009)
BACKGROUND: Sensitization to occupational allergens is frequently found in laboratory animal workers (LAWs) and can cause serious health problems. Atopy is a major risk factor for sensitization, but it is considered insufficient to advise against working with animals. OBJECTIVE: We investigated whether immunologic measures, including serology and cytokine production profiles of blood cells, and parameters for airway inflammation are associated with the development of occupational sensitization. METHODS: In a prospective cohort study 110 starting LAWs were followed for 2 years. At inclusion, results of health questionnaires, skin test results, lung function measures, methacholine threshold levels, and nasal lavage fluid were obtained. Blood was taken for measuring total IgE and allergen-specific IgE antibodies. Cytokine production profiles were measured in whole blood. RESULTS: Twenty-two new cases of sensitization were identified during follow-up. In multivariate logistic regression analysis a model including atopy and total IgE level predicted sensitization best. This was corroborated in a separate validation cohort. Parameters for airway inflammation or cytokine production profiles did not further contribute to the prediction of sensitization. Based on these results, pre-employment counseling aimed at applicant LAWs with atopy and a total IgE level of greater than 100 IU/mL might be able to reduce occupational sensitization by up to 45% to 50% with less than 10% false-positive predictions. CONCLUSION: The combination of atopy and total IgE level offered the best model to predict development of occupational sensitization. Other immunologic parameters and parameters of airway inflammation did not contribute significantly.
Keywords: Occupational allergy; atopy; IgE; laboratory animal allergy; sensitization; Coronacrisis-Taverne